Kompetensi Wirausaha Santri di Beberapa Pesantren di Jawa Barat dan Banten - U Maman; Amri Jahi (Jurnal Penyuluhan, 2009)
The student of pesantren (santri) should have integrated competencies, consist of Islamic knowledge, Islamic personalities, and entrepreneurship competencies. The Santri’s characteristics are predicted to contribute to the santri’s entrepreneurship competencies. For this assumption, the research objective is to know the contribution of santri’s characteristics, Islamic knowledge   and personalities to the santri’s entrepreneurship competencies. Data collecting was held during December 2006-April 2007 from the 158 students in 13 pesantren in West Java and Banten.  The santri’s characteristics include age, level of formal education, experience of business training before entering to the pesantren, parent job, perception of talent and interest. The variables contribute to the entrepreneurship competencies are proved the Islamic personalities, perception of talent, Islamic knowledge abilities, and interest.